Lipocalin 24p3 Induction in Colitis Adversely Affects Inflammation and Contributes to Mortality - Liu, Zhuoming; Cominelli, Fabio; Di Martino, Luca; Liu, Ruifu; Devireddy, Neha; Devireddy, Lax R.; Wald, David N. (Frontiers in Immunology, 2019)
Recognition of microorganism associated molecular patterns by epithelial cells elicits signaling cascades resulting in the production of host defense proteins. Lipocalin 24p3 is purported to be one such protein. 24p3 binds prokaryotic and eukaryotic siderophores and by sequestering iron laden bacterial siderophores it was believed to restrict bacterial replication. As such mice deficient for 24p3 are susceptible to systemic infections. However, it is not clear whether deficiency of 24p3 on the gut mucosa contributes to inflammation. In line with 24p3’s function as a bacteriostat, it would be reasonable to assume that deficiencies in the control of intestinal flora from 24p3 absence play a role in inflammatory intestinal diseases. Surprisingly, we show 24p3 is a contributor of inflammation and 24p3 deficiency protects mice from dextran sodium sulfate (DSS)-induced colitis. 24p3 was found to be a negative regulator of platelet-derived growth factor (PDGF), which helps maintain the integrity of the gut mucosa. Neutralization of PDGF-BB abrogated resistance of 24p3 null mice to DSS confirming the direct link between 24p3 and PDGF-BB. Finally, iron handling in wild-type and 24p3-null mice upon DSS treatment also differed. In summary, differential iron levels and enhanced expression of PDGF-BB in 24p3 null mice confers resistance to DSS.